Law Enforcement on Environmental Pollution by Nickel Mining Companies - Aris, Ahmad Wahfiudin; Angga, La Ode; Rugebregt, Revency Vania (Fakultas Hukum Universitas Pattimura, 2025)
Introduction: Environmental pollution in Indonesia has largely not been fully resolved, which should be the full responsibility of the company. One of the cases of environmental pollution that occurred in North Konawe Regency, Southeast Sulawesi Province.Purposes of the Research: The purpose of this research is to examine and analyze the responsibility of companies that commit environmental pollution and the form of law enforcement of companies that commit environmental pollution.Methods of the Research: This type of research is normative juridical research, which is legal research whose object of study includes the provisions of legislation or also called literature law research. Literature law research is research that is carried out by examining literature materials or secondary data.Results of the Research: The responsibility of PT. Virtue Dragon Nickel Industry (VDNI) which is suspected of environmental pollution that occurs includes preventive measures, waste management and recovery if environmental damage occurs, business actors are absolutely responsible. Civil Liability of PT. Virtue Dragon Nickel Industry (VDNI) includes installing waste management units so that waste is in accordance with the specified environmental quality standards, restoring environmental functions, increasing supervision and evaluation to anticipate the recurrence of negligence and carrying out moral responsibility to the environment by accelerating the process of restoring polluted river stream environments by carrying out routine cleaning of river flows so that waste residues that are polluted Exit into the river can quickly decompose. Civil law enforcement can be used as an instrument to hold PT. Virtue Dragon Nickel Industry (VDNI) which has been suspected of polluting the environment through a claim for compensation by the aggrieved party. Civil lawsuits can be filed on the basis of Unlawful Acts, where business actors are considered to have violated environmental rights and harmed other parties with their polluting actions.